Association Between Perinatal Outcomes and Mode of Conception in Twin Pregnancies [8B]. (May 2018) - Janssen, Ashley; Dahlke, Joshua; Hultgren, Elizabeth; Satpathy, Hemant; Bonebrake, Robert; Patel, Emily
Abstract : INTRODUCTION: Artificial reproductive technology (ART) is associated with increased risks of adverse perinatal outcomes in singleton gestations; however, the association in twin gestations is less clear. Minimal data exists on the impact of oral and injectable fertility medications on maternal and perinatal outcomes in twins. Our objective was to examine the impact of conception method on perinatal outcomes. METHODS: We performed a retrospective cohort of all twin pregnancies delivered in a single-tertiary care-center with ultrasound evaluation between 1/1/2013 and 4/1/2016. Women with unknown conception method, missing maternal or neonatal data, and monochorionic-monoamniotic twins were excluded. The primary outcome was maternal and neonatal morbidity in twin pregnancies conceived among three groups. RESULTS: Of 424 twin pregnancies during the study period, 417 met inclusion criteria. 199 conceived spontaneously (G1), 86 conceived through oral/injectable medications (G2), and 132 conceived through in-vitro fertilization (IVF) (G3). Compared to G1, G2 and G3 were more likely nulliparous, privately insured, diagnosed with preeclampsia (G2: P=.03; G3: P<.01), experienced greater rates of postpartum hemorrhage (G2: P=.02; G3: P<.01) and less likely to conceive monochorionic-diamniotic twins. No difference was noted in composite maternal or neonatal morbidity between groups. CONCLUSION: Twin gestations conceived via IVF or oral/injectable medications are similarly associated with an increased risk of preeclampsia and postpartum hemorrhage compared to spontaneous conception. Women who conceive by infertility treatment, regardless of the type, should be counseled regarding this increased maternal risk.